Fixed point theorems on expansion type maps in intuitionistic fuzzy metric space - Chauhan, MS; Singh, Bijendra; Singh, Bharat (Kathmandu University Journal of Science Engineering and Technology, 2011)
Ever since the introduction of fuzzy sets by Zadeh [1] , the fuzzyness invaded almost all the branches of crisp mathematics. Deng [3] kaleva and Seikalla [2] and Kramosil and Michalek [5]Have introduced the concept of fuzzy metric space, George and Veeramani [4] modified the concept of fuzzy metric space introduced by kramosil and michalek [5]. In thia paper effort has been made to obtain some results on fixed points of expansion type mapping in Intuitionistic fuzzy metric space